2019
DOI: 10.1136/bmjos-2017-000035
|View full text |Cite
|
Sign up to set email alerts
|

Did a change in Nature journals’ editorial policy for life sciences research improve reporting?

Abstract: ObjectiveTo determine whether a change in editorial policy, including the implementation of a checklist, has been associated with improved reporting of measures which might reduce the risk of bias.MethodsThe study protocol has been published at doi: 10.1007/s11192-016-1964-8.DesignObservational cohort study.PopulationArticles describing research in the life sciences published in Nature journals, submitted after 1 May 2013.InterventionMandatory completion of a checklist during manuscript revision.Comparators(1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 21 publications
2
43
0
Order By: Relevance
“…Previous studies have also found that providing additional specialized review based on reporting guidelines led to small improvements to manuscripts, while suggesting reporting checklists to regular reviewers had no effect (Cobo et al, 2007, 2011). Reporting guidelines and checklists provided to authors during the review or manuscript preparation processes have been reported to cause modest improvements limited to a few items in in vivo animal studies (Han et al, 2017; Leung et al, 2018; Hair, Macleod and Sena, 2019; The NPQIP Collaborative group, 2019). Thus, the intuitive expectation that quality of reporting should be an aspect of study quality that is easily amenable to improvement by peer review does not seem to be confirmed by the available data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have also found that providing additional specialized review based on reporting guidelines led to small improvements to manuscripts, while suggesting reporting checklists to regular reviewers had no effect (Cobo et al, 2007, 2011). Reporting guidelines and checklists provided to authors during the review or manuscript preparation processes have been reported to cause modest improvements limited to a few items in in vivo animal studies (Han et al, 2017; Leung et al, 2018; Hair, Macleod and Sena, 2019; The NPQIP Collaborative group, 2019). Thus, the intuitive expectation that quality of reporting should be an aspect of study quality that is easily amenable to improvement by peer review does not seem to be confirmed by the available data.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of each study was performed through an online questionnaire implemented on Google Forms. Questions were based on existing reporting guidelines (Moher et al, 2001; von Elm et al, 2007; Kilkenny et al, 2010; Bossuyt et al, 2015), journal checklists (Nature, 2013) and previous studies on quality of reporting (Hair, Macleod and Sena, 2019; The NPQIP Collaborative group, 2019), and are presented along with their response options on Table S1 . They were based on direct, objective criteria, in an attempt to avoid the need for subjective evaluation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A randomised controlled trial at PLOS ONE, for example, demonstrated that a request by journal staff to include a completed ARRIVE checklist in the manuscript submission process did not improve the disclosure of information in published papers [31]. In contrast, other studies using reporting checklists with more editorial follow up have shown a marked improvement in the nature and detail of the information included in publications [32][33][34]. Providing the level of journal or editorial input required to ensure compliance with all the items of the ARRIVE guidelines is unlikely to be sustainable for most journals because of the resources needed.…”
Section: Why Good Reporting Is Importantmentioning
confidence: 99%